Analisis Dampak Perusahaan Kelapa Sawit PT. Agriprima Cipta Persada terhadap Kesejahteraan Masyarakat - Anita Rusianti; Syamsidar Sinaga (Syntax Idea)
Viewed from an economic aspect, palm oil can support domestic industries based on palm oil-based products. Apart from that, the development of many economic centers in new regions will support regional development, and ultimately create job opportunities and reduce unemployment. This research uses a quantitative description method, namely a research approach that aims to describe or explain certain phenomena using numerical data and draw conclusions. The aim of this research is to determine the difference between the welfare conditions of the people of Elnggol Jaya Village before and after the establishment of the oil palm plantation company PT. Agriprima Cipta Persada. The conclusion that can be obtained is that based on the results of the sample scoring, the average level of welfare of the people of Elnggol Jaya village before the existence of PT. Aggriprima Cipta Persada was 14.3 points, whereas after the existence of PT. Agriprima Cipta Persada increased the level of community welfare by 21.9 points.